WOMEN'S ROLE IN STRENGTHENING RELIGIOUS ACTIVITIES THROUGH EMPOWERMENT OF THE HOUSE OF TAHFIZ DARUL JANNAH - Irwandi Irwandi; Zulamri Zulamri; Romi Maimori; Tri Yuliani (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
The role of women in Minangkabau plays a strategic place in fostering people, including in younger generation in "tahfiz’s house" activities. Problem that usually arises is the authority of women in doing activities outside, especially in the Nagari Tanjung Barulak. The women in Nagari Tanjung Barulak are not only active at home as Limpapeh Rumah Gadang who act as mothers for the children but also as "mothers" for children in Nagari. The research method used is a qualitative research method with a descriptive approach. The techniques of Data collection are interviews, observation and documentation. The result of research shows that women has vital roles in stir Tahfiz's house in Nagari Tanjuang Barulak, Batipuh District. It means there was no contradiction in fostering people in terms of religion. In terms of Minangkabau customs, the role of women also has its own place, and can play a role in two functions, namely the function as mother or Bundo Kanduang in the community and family as well as Bundo Kanduang in the midst of the people.